Data from a public–industry partnership for enhancing corn nitrogen research. (6th September 2021) - Ransom, Curtis J.; Clark, Jason; Bean, Gregory Mac; Bandura, Chris; Shafer, Matthew E.; Kitchen, Newell R.; Camberato, James J.; Carter, Paul R.; Ferguson, Richard B.; Fernández, Fabián; Franzen, David W.; Laboski, Carrie A.M.; et al.
Abstract: Improving corn ( Zeamays L.) N managementis pertinent to economic andenvironmental objectives. However, there are limited comprehensive data sources to develop and test N fertilizer decision aid tools across a wide geographic range of soil and weather scenarios. Therefore, a public‐industry partnership was formed to conduct standardized corn N rate response field studies throughout the U.S. Midwest. This research was conducted using a standardized protocol at 49 site‐years across eight states over the 2014–2016 growing seasons with many soil, plant, and weather related measurements. This note provides the data (found in supplemental files), outlines the data, summarizes key findings, and highlights the strengths and weakness for those who wish to use this dataset. Core Ideas: Data provided from 49 corn N response trials in eight states across the U.S. Midwest. Data included a wide range of soil, plant, and weather measurements. Published manuscripts show potential methods to improve N management.